2018
DOI: 10.1177/0954411918806333
|View full text |Cite
|
Sign up to set email alerts
|

Density estimation based on the Hounsfield unit value of cone beam computed tomography imaging of the jawbone system

Abstract: The aim of this study is to investigate the estimation of density from the Hounsfield unit of cone beam computed tomography data in dental imaging, especially for dental implant application. A jaw phantom with various known densities of anatomical parts (e.g. soft tissue, cortical bone, trabecular bone, tooth enamel, tooth dentin, sinus cavity, spinal cord and spinal disc) has been used to test the accuracy of the Hounsfield unit of cone beam computed tomography in estimating the mechanical density (true densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Predicting cortical bone densities and thickness by cortical shells of the ROIs using clinical CT provided excellent correlations with micro CT results 29,30 . The accuracy of bone densities calculated from Hounsfield units (HUs) from CT data has been demonstrated 31 , and three-dimensionally (3D) reconstructed axial CT images could accurately define the border of the cortical bone 32,33 . Therefore, owing to advances of 3D-modeling technology using CT images, cortical bone density and thickness of craniofacial structures could be evaluated in routine clinics.…”
mentioning
confidence: 99%
“…Predicting cortical bone densities and thickness by cortical shells of the ROIs using clinical CT provided excellent correlations with micro CT results 29,30 . The accuracy of bone densities calculated from Hounsfield units (HUs) from CT data has been demonstrated 31 , and three-dimensionally (3D) reconstructed axial CT images could accurately define the border of the cortical bone 32,33 . Therefore, owing to advances of 3D-modeling technology using CT images, cortical bone density and thickness of craniofacial structures could be evaluated in routine clinics.…”
mentioning
confidence: 99%
“…The Hounsfield Scale (HU) was used to understand bone regeneration. Bone density measurements from X-ray absorption, generate attenuation coefficients used to measure degenerative bone changes, and provide parameters for planning oral rehabilitation with osseointegrated implants 19,20 . For our study, the HU Scale was a measure of bone healing, and demonstrated that S53P4 maintained high tissue attenuation coefficients, without necessarily indicating bone consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…For bone regeneration analyses, T1 and T2 tomograms were compared. Parameters included bone attenuation density/coefficients, and followed the Hounsfield Scale 19 , 20 . To this end, coordinates X/Y were located in the linear half of bone gaps, using the cursor in the 2D function of the Radiant DICOM viewer software (Medixant).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, conventional CT scans are not only able to provide information in association with fracture patterns [9] but also provide additional information on bone properties, which are therefore called "opportunistic osteoporosis CT scans" [10]. Owing to the advances in 3D graphic processing technologies, the measurement of the thickness and density of the cortical bone in the target region of interests (ROI) using CT data has become possible [11,12]. Specifically, the average Hounsfield Unit (HU) and cortical bone thickness can be automatically calculated using a 3D graphic processing software.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in 3D graphic processing technology has made the evaluation of the cortical bone quality possible based on conventional CT images, especially in the craniofacial field [11,22]. The validity and reliability of such an assessment method in association with the measurement of the cortical bone density in the craniofacial field have been shown [11]. However, few studies have investigated the qualities of extremity skeletal cortical bone with the application of this technology [12].…”
Section: Introductionmentioning
confidence: 99%